2015
DOI: 10.4028/www.scientific.net/amm.766-767.780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Duplex Stainless Steel/Cold Reduced Low Carbon Steel Dissimilar Weld Joints by GTAW

Abstract: The purpose of this study is to evaluate the mechanical and metallurgical properties of dissimilar metal weld joints between duplex stainless steel/Cold Reduced low carbon Steel (CRS) by Gas Tungsten Arc Welding (GTAW) process. The dissimilar 2 mm thickness plates of duplex stainless steel and cold reduced low carbon steel, conforming to AISI 2205 and IS 513_2008 CR2_D were butt welded by means of gas tungsten arc welding using argon as shielding gas. The butt welding joint arrangement was used for this experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It was reported that the weld zone (WZ) of GTAW welds may show an acceptable γ/α ratio by using a special filler rod. However, the weld microstructure features are not similar to its base metal microstructure [ 11 ], and the productivity is low, as the maximum thickness that can be welded in single pass cannot exceed 3 mm [ 2 , 12 ]. The GTAW process using nickel-enriched filler rod ER 2209 provides an acceptable α/γ ratio in the weldments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the weld zone (WZ) of GTAW welds may show an acceptable γ/α ratio by using a special filler rod. However, the weld microstructure features are not similar to its base metal microstructure [ 11 ], and the productivity is low, as the maximum thickness that can be welded in single pass cannot exceed 3 mm [ 2 , 12 ]. The GTAW process using nickel-enriched filler rod ER 2209 provides an acceptable α/γ ratio in the weldments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%